Determinants of Academic Performance of Undergraduate Students in Private Universities in Bangladesh: A Case Study (Global Journal of Human-Social Science, 2018)
Most of the existing literature studying the determinants of academic performance of undergraduate students in both public and private universities in Bangladesh are qualitative in nature. In this study, a combination of both qualitative and quantitative analysis has been done. Analyses were done using data collected from 605 students of several departments of International University of Business Agriculture and Technology (IUBAT), a private university located in Dhaka, the capital of Bangladesh. Statistical association between academic performance and several explanatory variables was checked. Variables such as type of department, result of pre-university public examinations, gender, class attendance, teacher-student relationship, self-confidence level of the students, depression and amount of credit hours completed were found to impact the academic performance level significantly. The findings of this study would help students, teachers and concerned authority of the institution to comprehend the factors impacting academic performance of the students and take further actions accordingly.
Keywords: academic performance; demographic variables; socio-economic variables; institutional variables; logistic regression analysis